Italian Cities SDGs Composite Index: A Methodological Approach to Measure the Agenda 2030 at Urban Level - Luca Farnia; Laura Cavalli; Sergio Vergalli (Fondazione Eni Enrico Mattei (FEEM), 2019)
In this paper we calculate the Italian Cities Sustainable Development Goals (SDGs) Composite Index potentially useful for policy analysis and dissemination of sustainable development at local level in Italy. Structured into several dimensions representing 16 out of 17 SDGs adopted by the United Nations at the end of September 2015, the index merges 53 available economic, social and environmental elementary indicators into a single composite dimension, highlighting a geographical and demographic heterogeneity within the country. By using the Spectral Value Decomposition technique, the index offers an urban focus of sustainability, showing some differences among the goals and the cities of Italy. Finally, it identifies the Goal concerning quality education and decent work and economic growth as the main key Goals for sustainability.
Keywords: C4; O18; Q56; 330; SDGs; Composite Index; Weighting; Correlation; Spectral Value Decomposition; Principal Component